Protonation-Dependent Luminescence of an Iridium(III) Bibenzimidazole Chromophore - Rommel, Sebastian A.; Sorsche, Dieter; Rockstroh, Nils; Heinemann, Frank Wilhelm; Kuebel, Joachim; Waechtler, Maria; Dietzek, Benjamin; Rau, Sven (European Journal of Inorganic Chemistry, 2015)
We present the synthesis and a detailed structural and photophysical investigation of the bis(phenylpyridine)iridium(III) complex of 4,4,5,5-tetramethyl-2,2-bibenzimidazole [Ir(tmBBI)-H-2] and its homodinuclear complex [Ir(tmBBI)Ir]. Their structures were determined by single-crystal X-ray diffraction analysis and NMR spectroscopy, and detailed UV/Vis and emission spectroscopy studies were performed. Ir(tmBBI)-H-x shows strong protonation-state-dependent luminescence and is luminescent in all three of its protonation states, which allows for protonation-state-dependent color tuning from the green to blue spectral region. The diastereomeric meso and rac forms of the dinuclear Ir(tmBBI)Ir could be separated by fractional crystallization and both showed strong luminescence. A comparison with structurally related ruthenium complexes showed pronounced differences in their photophysical properties.
Keywords: Iridium; Hydrogen bonds; Photophysics; Luminescence; Chromophores; Color tuning